Religiusitas, Islamic Branding terhadap Keputusan Konsumen Berbelanja pada Ritel Modern dan Tradisional - Muhammad Naufal Hidayat (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
This study aims to analyze the influence of religiosity and Islamic Branding / Halal Label on consumer decisions to shop at modern and traditional retailers in Banda Aceh City. The method used in this research is a quantitative method with an explanatory approach and using a questionnaire instrument. The data collection technique is primary using purposive sampling technique. Data analysis using multiple linear regression. The place of research is in the city of Banda Aceh. The data used are primary data obtained through a questionnaire instrument. Data collection techniques using purposive sampling technique. Data analysis using the statistical method of multiple linear regression analysis. The results showed that Religiosity (X1) and Islamic Branding / Halal Label (X2) influenced consumer decisions in shopping at modern retailers in Banda Aceh City by 0.596 and 0.377, respectively. Meanwhile, in traditional retail, Religiosity (X1) and Islamic Branding / Halal Label (X2) affect consumer decisions in shopping by 0.057 and 0.395, respectively.